Efektivitas penerapan SIMKAH di KUA Kecamatan Poncol Kabupaten Magetan perspektif efektivitas hukum Soerjono Soekanto - Muhroni, Tedy (Maliki Interdisciplinary Journal, 2024)
Marriage is a bond between a man and a woman that is based on law. A legal marriage is a marriage that is registered with an official institution and has the authority in its field, in this case, the Office of Religious Affairs. The purpose of marriage registration is to provide legal protection to married couples who have married and provide legal protection to children born from marriage. Along with the times, marriage registration has developed with the launch of the SIMKAH application, an online-based application used to input and manage prospective bride and groom data online with good data security quality. The implementation of SIMKAH in one Religious Affairs Office with another Religious Affairs Office is certainly different in terms of the effectiveness of its application. In the application of SIMKAH in the Poncol District Religious Affairs Office, it is reviewed from the perspective of Soerjono Soekanto’s legal effectiveness which is analysed with several factors that influence legal effectiveness, namely the legal factors themselves, law enforcement factors, infrastructure factors, community factors, and cultural factors, so that later it will get the results of several indicators there.